1999
DOI: 10.1080/080352599750030095
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of primary nocturnal enuresis and attention deficit hyperactivity disorder

Abstract: Primary nocturnal enuresis (PNE) is a prevalent disorder among children with a complex mode of inheritance. Family, twin, and linkage studies have provided evidence that genetic factors underlie the familiality of PNE. Linkage investigations support the hypothesis that PNE is heterogeneous, and the genetic heterogeneity may be reflected in co-morbid clinical conditions such as attention deficit hyperactivity disorder (ADHD). This study used a family study method and examined the transmission of PNE in relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 19 publications
0
11
0
1
Order By: Relevance
“…Furthermore, a centrally located ADHD-inattentive dysfunction exerts a negative effect on arousability and brainstem signaling in enuresis 35,36. However, the results of a family study suggest that ADHD and enuresis are etiologically independent 37. Other researchers suggested that increased behavioral symptoms reflect coping behavior for dealing with the emotional and social burden of enuresis 9,29,38.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a centrally located ADHD-inattentive dysfunction exerts a negative effect on arousability and brainstem signaling in enuresis 35,36. However, the results of a family study suggest that ADHD and enuresis are etiologically independent 37. Other researchers suggested that increased behavioral symptoms reflect coping behavior for dealing with the emotional and social burden of enuresis 9,29,38.…”
Section: Discussionmentioning
confidence: 99%
“…enuresis is caused by the undiagnosed ADHD, such that children get distracted from going to the bathroom) or whether both outcomes are influenced by a shared vulnerability that is associated with increased risk for both conditions at different points in development 16 . Family studies indicate that ADHD and enuresis are transmitted independently 38 . However, other studies indicate that the combination of enuresis and ADHD shows different neurophysiological, attentional, and clinical correlates compared to both children with only enuresis or only ADHD, raising the possibility that children who have both enuresis and ADHD may be an etiologically distinct subgroup 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Similar group comparisons were assessed by Bailey et al. . The authors compared children with primary NE only, ADHD only, primary NE + ADHD and nonaffected controls to determine whether primary NE and ADHD share a genetic basis.…”
Section: Discussionmentioning
confidence: 99%
“…Bailey et al. examined the transmission of primary NE in relatives of primary NE patients and controls, with or without ADHD, to determine whether primary NE and ADHD share a genetic basis. As suggested, primary NE was shown to be highly familial, but the rate of primary NE in first‐degree relatives was independent of the presence of comorbid ADHD.…”
Section: Introductionmentioning
confidence: 99%